2013
DOI: 10.1080/19443994.2013.781731
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and adsorption performance of molecularly imprinted polymers for Kaempferol

Abstract: A B S T R A C TMolecularly imprinting polymers (MIPs) are a class of highly cross-linked polymer with specific binding sites for a target molecule. In this study MIPs were prepared by precipitation polymerization, using kaempferol as the template molecule, methacrylic acid as the functional monomer, azodiisobutyronitrile as the initiator, and ethylene glycol dimethacrylate as the cross-linker in acetonitrile solvent. The synthesized kaempferol-MIP and nonimprinted polymer (NIP) were analyzed by infrared spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In addition, the slope of plot a1 (−1.35) was lower than that of plot a2 (−0.42), which indicated that the amounts of high affinity sites were higher in MIP-4VP, while the Scatchard plot for MIP-AM was only a single straight line. The linear regression equation was Q / C = −0.42 Q + 19.54 ( R 2 = 0.94, b1), suggesting that homogeneous recognition sites for quercetin were formed in MIP-AM. , K d and Q max were calculated to be 5.14 μg/mL and 78.84 μg/g, respectively (MIP-AM, Table S1 b1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the slope of plot a1 (−1.35) was lower than that of plot a2 (−0.42), which indicated that the amounts of high affinity sites were higher in MIP-4VP, while the Scatchard plot for MIP-AM was only a single straight line. The linear regression equation was Q / C = −0.42 Q + 19.54 ( R 2 = 0.94, b1), suggesting that homogeneous recognition sites for quercetin were formed in MIP-AM. , K d and Q max were calculated to be 5.14 μg/mL and 78.84 μg/g, respectively (MIP-AM, Table S1 b1).…”
Section: Resultsmentioning
confidence: 99%
“…The linear regression equation was Q/C = −0.42Q + 19.54 (R 2 = 0.94, b1), suggesting that homogeneous recognition sites for quercetin were formed in MIP-AM. 28,38 K d and Q max were calculated to be 5.14 μg/mL and 78.84 μg/g, respectively (MIP-AM, Table S1 b1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The Scatchard equation is an equation used to describe the interaction between adsorbed materials and imprinted molecules in the adsorption process. The analysis of adsorption isotherm data with this equation is helpful in obtaining information about the affinity of adsorption sites and the maximum adsorption capacity [ 22 , 23 ]. The specific data are shown in Table 2 and Figure S2 .…”
Section: Resultsmentioning
confidence: 99%